Kajian Yudisial: Perlawanan Para Pihak (Partij Verzet) dalam Proses Eksekusi Hak Milik Atas Tanah Berdasarkan Hukum Acara Perdata - Putri, Azizah Kamilah; Hazar Kusmayanti; Artaji Artaji (JUSTISI, 2024)
Court decisions that have legal force must be complied with, and execution carried out if the losing party does not voluntarily comply with the judgment. Issues arise when the losing party appeals or takes other legal actions, delaying execution and creating legal uncertainty. Execution is applicable only to condemnatory judgments and is often obstructed by respondent's resistance, a legal challenge from the party involved in the case. The researcher highlights three cases of legal resistance efforts: the South Jakarta District Court decision number 518/Pdt.G/1999/PN Jkt.Sel, Kendal District Court decision number 20/Pdt.Bth/2021/PN Kdl, and Kendal District Court decision number 9/Pdt.Bth/2022/PN Kdl. This study employs a normative juridical method, examining descriptive-analytical literature, and utilizes a qualitative juridical approach in analysis. The research reveals discrepancies between legal certainty theory and judicial practice, where cases may not align with facts or legal standing, leading judges to reject such requests. The study concludes that respondent's resistance is a legal recourse available to the executed party against execution, which does not automatically suspend execution unless there are clear and accepted grounds recognized by the court. The Indonesian Civil Code (HIR) and Civil Procedure Law (RBg) provide legal certainty and protect the rights of those aggrieved by court decisions through the mechanism of respondent's resistance.